Legal Analysis of Abortion in Cases of Anencephaly: A Study of Moral, Criminal Law, and Health Perspectives - Rezqinna, Maulidya; Sukarya, Wawang S (Intellectual Law Review (ILRE), 2024)
Abortion is a controversial issue in society, related to moral and legal values. In Indonesia, abortion regulations are found in Law No. 1/1946 of the Criminal Code (KUHP) and Law No. 17/2023 of the Criminal Code, as well as the Health Law. Public perspectives are divided between those opposed to and in favour of abortion, particularly in the context of anencephaly. Maternal health is a focus, with the World Health Organization (WHO) emphasising the need for safe access to abortion. This study analyses the legal framework related to abortion in Indonesia, focusing on anencephaly, and identifies public views. A normative juridical method was used to review the relevant regulations. The results show a mix of criminal and health law regulations, reflecting concern for women's rights and ethical values. However, implementation still faces barriers, including availability of health facilities and consistent law enforcement. An in-depth understanding of people's moral perspectives is needed to design inclusive and sustainable policies on abortion, particularly in cases of anencephaly.